INFLUENCE OF ASSET STRUCTURE, CAPITAL STRUCTURE, COMPANY SIZE AND CORPORATE SOCIAL RESPONSIBILITY TOWARDS FIRM VALUE WITH EARNING GROWTH AS INTERVENING VARIABLE IN STATE-OWNED ENTERPRISES LISTED ON THE INDONESIA STOCK EXCHANGE (STUDY ON NON-BANK SOE S - Muhamad Sanusi Efendi; Ontot Murwanto; Tri Ratnawati (Universitas 17 Agustus 1945 Surabaya, 2022)
The purpose of this study was to determine how the influence of asset structure (X1), capital structure (X2), firm size (X3), corporate social responsibility(X4) on firm value (Y) with earning growth (Z) as an intervening variable in non-bank state-owned companies listed on the Indonesian stock exchange. 2018-2020 period. The sample companies are 10 non-bank state-owned companies. This research uses SEM-PLS, the software is smartPLS. Of the 13 significant hypotheses accepted, there are 3, namely asset structure on earning growth, capital structure on earning growth and firm size on firm value. There are 10 hypotheses that are not significant or rejected, namely asset structure to firm value, capital structure to firm value, firm size to earnings growth, corporate social responsibility to earnings growth, corporate social responsibility to firm value, earning growth to firm value, asset structure to firm value. firm value through earning growth as an intervening variable, capital structure on firm value through earning growth as an intervening variable, firm size on firm value through earning growth as an intervening variable, corporate social responsibility on firm value through earning growth as an intervening variable Keywords : Asset structure, capital structure, company size, corporate social response, earning growth, firm value.